TYPOLOGIA REŻIMU ODPŁYWU RZEK W POLSCE W RÓŻNYCH FAZACH OSCYLACJI PÓŁNOCNOATLANTYCKIEJ - Wrzesiński, Dariusz (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
The paper presents the spatial distribution of types of river regime in Poland according to the assumptions of Dynowska (1997) for three time scales: 1971–2010 and for years with high and low indices of the North Atlantic Oscillation and directions of their transformation in various phases of NAODJFM. The paper applied daily flow values from the period 1971–2010 for 516 stations located on 280 Polish rivers. In the examined time scales, five types of regime were designated including rivers characterised by a similar distribution and range of monthly runoff values in an average annual cycle. The designated groups, however, differ in terms of the number of rivers, which affects the image of spatial distribution of rivers representing the identified types of regime. The analysis shows that in the studied NAODJFM phases, transformations of the flow regime of many rivers in Poland are often observed. Compared to average conditions (1971–2010), in the negative phase of NAODJFM, the most stable is nival type well formed. The most common transformations relate to the nival regime moderately formed, which usually changes into a nival well formed or nival-pluvial regime. In the positive phase of NAODJFM, regime transformations are more frequent. The most stable type of regime is again nival well formed, and the most common transformation occurs in the case of the pluvio-nival regime (into the nival-pluvial regime) and nival-pluvial regime, which is transformed into well or moderately formed nival regimes.